Women's drinking decisions in sexually risky situations: Effects of a low level of intoxication. (August 2015) - Noel, Nora E.; Daniels, Karen A.; Ogle, Richard L.; Maisto, Stephen A.; Lee A., Jackson; Ehlke, Sarah J.; Carroll, Mallorie G.
Abstract: Introduction: Alcohol administration studies assessing alcohol's deleterious effects on women's threat perception and response in potential sexual assault situations usually employ a moderate to high dose (.07% BAC or more) and measure alcohol's effects specifically on women's sexual decisions. The current study used a low dose (.03%, equivalent to about 1–2 drinks) to assess women's projected decisions on a different risky behavior: decisions to continue drinking and to drink higher amounts in a series of ecologically-valid sexual risk situations. Methods: Young adult women ( n  = 17; M age = 21.8, SD = 1.3, range 21–25) participated in a three-session double-blind within subjects 2 (type of scenario) × 3( beverage) experiment, responding each time to 6 vignettes with an attractive man who was either Familiar or had Just Met her. In each session participants consumed a beverage (alcohol, placebo or water, random order) and projected emotional reactions and drinking decisions (likelihood and amount) in each of the 6 scenarios. Results: Regardless of beverage, women predicted greater happiness, drinking likelihood, and drinking amount with "Familiar" men. However, there was also an interaction: they projected increased subsequent amounts in the .03% BAC (vs. water and placebo) condition differentially in the "Familiar" scenarios. Conclusion: When the woman is Familiar with the man in a risky sexual situation, just one drink may increase subsequent projected alcohol amount over that originally intended. Implications include a low dose as a possible prime for more drinking, increasing sexual assault risk. Highlights: Alcohol administration study with young adult women 2 (familiar versus just met man) x 3 (beverage type) within subjects design Consumed water, placebo or low alcohol dose Responded to 6 vignettes with likelihood to drink more and projected amount Interaction: .03 BAC led to increased planned amounts with "Familiar" man only